Anti-vascular endothelial growth factor agents for diabetic maculopathy. Issue 7 (24th June 2009) - Salam, A; DaCosta, J; Sivaprasad, S
Abstract : The management of diabetic macular oedema is changing. The therapeutic armamentarium for diabetic macular oedema (DMO) includes a new group of drugs that inhibit vascular endothelial growth factor (VEGF). These anti-VEGF agents are already being used widely in DMO in clinical practice despite that several phase III trials on these drugs are still underway. There are no established protocols on the use of these agents in DMO, but short-term results are appealing. This review provides an update on the use of anti-VEGF agents in DMO. Although intravitreal delivery of anti-VEGF agents is a relatively safe procedure, the long-term local and systemic effects of these agents in the diabetic population remain unknown. In this regard, this review also highlights the need for close surveillance of the use of these drugs in this high-risk population.